The postglacial sea level rise within the Guadiana Estuary- a contribution to a regional record in the Gulf of Cadiz - Boski, T. (2013)
In the Guadiana River Estuary, the Holocene estuarine infill is underlain by coarse delta fan sediments enclosing saltmarh deposits, dating back to isotope stage 5e or a stage 3 interstadial highstands.